SOSIALISASI DAN PEMBINAAN BUDIDAYA IKAN DALAM EMBER UNTUK KETAHANAN PANGAN - Juniarti Juniarti; Nazwirman Nazwirman; Indra Kusuma (Universitas Islam kalimantan MAB, 2020)
The food crisis can be carried out only in Indonesia as a result of the Covid-19pandemic. Concrete steps are carried out using empty yards around the housing. Thisactivity provides sanitation fishers with knowledge and practices of fish cultivation inBanjar Wijaya Housing Tangerang City. On average they are married and their incomeis insufficient. The implementation method used is socializing in the form of counselingand assistance. Stages of activities carried out provide knowledge and arrange thenecessary tools and manufacture of fish farming in buckets and vegetables. The selectedfish is oxygen resistant. Maintenance for 42 days produces catfish and kale harvest. Thisactivity should increase the participants' knowledge from the average of the correctanswers.